The Story of Prophet Adam and the Creation of Humanity: An Analysis of Human Origins - Ubaidillah, Muhammad Adam; Daffah, Ahibbah Mynessa Anna; Karima, Tshelitsha Laily Nurfaizah (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to analyze the story of Prophet Adam as the first human from an Islamic perspective and to examine the origins of humanity through both theological and scientific approaches. The main focus of this research is to understand the narrative of Prophet Adam in the Qur’an and the concept of human creation in religion and science, particularly regarding Adam’s role, while comparing it to the theory of evolution and uncovering the meaning of life’s purpose from a Qur’anic perspective. The method used is a qualitative study with a library research approach, involving the analysis of religious texts and relevant academic sources using content analysis. The findings reveal that the Islamic narrative of human creation contains not only spiritual and moral values but also implies complex existential dimensions. On the other hand, modern science provides an evidence-based explanatory framework that emphasizes the biological processes involved in human evolution. This study finds that despite the paradigm differences between religion and science, both can be positioned in a dialogical relationship in the effort to understand the origins of humanity holistically. In conclusion, the integration of theological and scientific approaches can enrich discourse on human existence and open pathways for interdisciplinary knowledge synthesis.